Critical Discourse Analysis Using Teun A. van Dijk’s Model on the Language of Power in Al Arabiya Online News Reporting: “The Israeli Army: All Options Are Open” Regarding the Possibility of a Ground Attack in Lebanon - Sabila, Jihan (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Language is not merely a neutral communication tool but an instrument of power capable of shaping public perception through the construction of ideology within media texts. This study aims to analyze the construction of power language in online media reporting concerning the conflict between Israel and Hezbollah. The primary focus is to reveal how language is utilized to build military legitimacy and influence public views regarding the escalation of ground attacks in Lebanon. The research method employed is descriptive qualitative with Teun A. van Dijk’s Critical Discourse Analysis (CDA) approach. Primary data were obtained from an Al Arabiya news article titled “Israeli Army: All Options Are Open.” Data analysis was conducted through three levels of discourse structure: macrostructure (thematic), superstructure (schematic), and microstructure (semantic, syntactic, stylistic, and rhetorical). The results indicate that at the macro level, the text is dominated by the theme of legitimizing Israel’s self-defense. At the superstructure level, the narrative is organized to emphasize non-negotiable military firmness. At the micro level, the use of militaristic diction, active sentences demonstrating subject dominance, and the exclusion of the opposing party’s perspective construct a one-sided narrative that positions Israel as the defensive party and Hezbollah as the aggressor. The conclusion of this study confirms that the news text contains non-neutral ideological content and serves as a means to drive public opinion for the sake of political and military legitimacy.